Effect of Processing Methods on Bioactive Components and Antioxidant Activity of Beetroot (Beta vulgaris L.) (Tribhuvan University Journal of Food Science and Technology, 2022)
Beetroot (Beta vulgaris L.) is known as antioxidant, anti-inflammatory, hepato-protective and anticancer due to its bioactive components. The effect of processing (blanching, open pan cooking, pressure cooking, microwave oven treatment, electric oven treatment and drying) on the bioactive components (total phenolic and total betalain content) and antioxidant activity in beetroot were studied. The total betalain content (676.03 mg/100g db) included betacyanin (445.64 mg/100g db) and betaxanthin (230.39 mg/100g db). Total phenolic content, total betalain content and antioxidant activity were significantly different (p